Quantitative Analyses of Antagonism: Combinations of Midazolam and Either Flunitrazepam or Pregnanolone in Rhesus Monkeys Discriminating Midazolam - Gerak, Lisa R. (The American Society for Pharmacology and Experimental Therapeutics, 2012)
Adverse effects of benzodiazepines limit their clinical use; these effects might be reduced without altering therapeutic effects by administering other positive GABA(A) modulators (i.e., neuroactive steroids) with benzodiazepines. One concern with this strategy involves reversing these combined effects in case of overdose. The current study examined whether flumazenil can attenuate the combined effects of two benzodiazepines, midazolam and flunitrazepam, and the combined effects of midazolam and the neuroactive steroid pregnanolone, in four monkeys discriminating midazolam. Each positive modulator produced ≥80% midazolam-lever responding. Interactions between midazolam and either flunitrazepam or pregnanolone were additive. Flumazenil antagonized the benzodiazepines when they were administered alone or in combination. Schild analyses yielded slopes that did not deviate from unity, regardless of whether benzodiazepines were administered alone or together; the pA(2) value for flumazenil was 7.58. In contrast, flumazenil enhanced the effects of pregnanolone with 0.32 mg/kg flumazenil shifting the pregnanolone dose-effect curve 2-fold leftward. Flumazenil attenuated the combined effects of midazolam and pregnanolone, although antagonism was not dose-dependent. Thus, the interaction between two benzodiazepines was similar to that of a benzodiazepine and a neuroactive steroid; however, flumazenil more efficiently attenuated a combination of two benzodiazepines compared with a combination of a benzodiazepine and a neuroactive steroid. Although the magnitude of antagonism of a benzodiazepine combined with a neuroactive steroid was reduced, these results support continued exploration of the use of combinations of positive modulators to enhance therapeutic effects while reducing adverse effects.